Health knowledge and livelihood experiences with COVID-19 amongst Arizona residents - Fingesi, Tina; Chung Yon, Lin; Soto, Sheila; Rosales, Cecilia (Frontiers in Public Health, 2022)
The Coronavirus disease 2019 (COVID-19) pandemic is an ongoing public health concern that is rapidly evolving and has impacted individuals and communities differently. We analyzed deidentified survey datasets to evaluate the perceptions, experiences, and impacts of COVID-19 among Arizona residents. The survey included 1,472 eligible Spanish-speaking participants in Southern (Pima, Santa Cruz, Cochise, Yuma County) and Central Arizona (Maricopa County). Eighteen questions which included participants' health and socio-economic status, source of information on COVID-19, preventive measures, the impact of COVID-19 on household income, and vaccination status were administered to the survey respondents. The analyzed data showed an unequal proportion of the reported source of COVID-19 information between Southern and Central Arizona participants. More male respondents (n = 833, 57%) participated in the study than did the female respondents (n = 638, 43%). Of the 1,472 total participants in both regions, 1,011 (68.7%) participants represented Southern Arizona while 461 (31.3%) participants represented Central Arizona. Of the 461 participants in Central Arizona, the majority reported television (56%) and social media (20%) as their primary source of information. Whereas, of the 1,011 participants in Southern Arizona, the majority reported social media (37%) and television (32%) as their major source of information on COVID-19. Overall, 82% of the participants were vaccinated, with a statistically significant difference between the proportion of vaccinated individuals in the Southern and Central Arizona (chi-square p-value of 0.00139). More individuals in Southern Arizona participated in the survey than in Central Arizona across both genders, with 58% of women reporting loss of jobs due to COVID-19. This study demonstrated that the COVID-19 pandemic profoundly had a more socio-economic impact on women than men, particularly Hispanic women in this subset.